Processing Of Coarse Sand From Terengganu Silica Sand - Mohd Hilmi, Mohamad Suffian (Universiti Sains Malaysia, 2018)
Coarse silica sand normally contains more impurities compared to the fine grain sand. Therefore, silica content in coarse sand is lower than fine grain. In this project, coarse silica sand was characterized with the tests of particle size distribution, grain scale, microscope analysis which can guide to the upgrading process by using common physical method that used in industry. The coarse sand was ground to reduce the size and liberate the impurities from the silica. Then, the silica content can be upgraded by remove or separate the impurities by spiral separator. The market of high grade silica sand is high due to the various applications can be done by using silica. The producer of silica has to be excited to rise the production. The increasing of silica content show it is a good method to apply. So, I believed that physical processing can upgrade the silica content and can produce high grade of silica for glass making industry.